Mid-term effects of wildfire and salvage logging on gross and net soil nitrogen transformation rates in a Swedish boreal forest - Ibáñez, T. S. (2022)
Wildfires are natural and important disturbances of boreal forest ecosystems, and they are expected to increase in parts of the boreal zone through climate warming. There is a broad understanding of the immediate effects of fire on soil nitrogen (N) transformation rates, but less is known about these effects several years after fire. In July 2014, a large wildfire in the boreal forest zone of Central Sweden took place. Four years after the wildfire, we measured processes linked to the soil N cycle using the 15N pool dilution method (for gross N mineralization, consumption and nitrification) and the buried bags method (for net N mineralization), in soils from stands of different fire severity that had or had not been subjected to salvage logging. Gross N mineralization and consumption rates per unit carbon (C) increased by 81 % and 85 % respectively, in response to high fire severity, and nitrification rates per unit C basis decreased by 69 % in response to high fire severity, while net N mineralization was unresponsive. There was no difference in the effect of salvage logging across stands of differing fire severity on N transformation rates, although concentrations of resin adsorbed nitrate (NO3–) were overall 50 % lower in logged compared to unlogged stands. We also found that irrespective of burn severity, N immobilization rates exceeded N nitrification rates, and immobilization was therefore the dominant pathway of gross N consumption. Gross N consumption rates were higher in burned than unburned stands, despite there being a higher active microbial biomass in unburned soil, which suggests an even higher immobilization of N over time as the microbial biomass recovers following fire. Our study shows that soil N transformation rates were more affected by changes in fire severity than by salvage logging, and that four years after the fire many aspects of the N cycle did not differ between burned and unburned stands, suggesting substantial resilience of the N cycle to fire and salvage logging. However, we note that long term impact and many additional ecosystem properties or processes should be evaluated before concluding that salvage logging has no ecosystem impact. Furthermore, shortened fire regimes following climate warming accompanied with shorter intervals between salvage logging practices, could still impact the capability for the N cycle to recover after an intense fire. While wildfire in the boreal region results in a shift from nutrient conserving to nutrient demanding plant species, our results suggest this shift is dependent on a relatively short-lived pulse of higher N cycling processes that would have likely dissipated within a few years after the fire.